Fixed Point Theorems for Asymptotically Contractive Multimappings - M. Djedidi; K. Nachi (International Journal of Mathematics and Mathematical Sciences)
We present fixed point theorems for a nonexpansive set-valued mapping from a closed convex subset of a reflexive Banach space into itself under some asymptotic contraction assumptions. Some existence results of coincidence points and eigenvalues for multimappings are given.